Mortality and the Business Cycle: Evidence from Individual and Aggregated Data - Gerard J. van den Berg; Ulf-G. Gerdtham; Stephanie von Hinke Kessler Scholder; Maarten Lindeboom; Johannes Lissdaniels; Jan Sundquist; Kristina Sundquist (Institute of Labor Economics (IZA), 2017)
There has been much interest recently in the relationship between economic conditions and mortality, with some studies showing that mortality is pro-cyclical whereas others find the opposite. Some suggest that the aggregation level of analysis (e.g. individual vs. regional) matters. We use both individual and aggregated data on a sample of 20-64 year-old Swedish men from 1993 to 2007. Our results show that the association between the business cycle and mortality does not depend on the level of analysis: the sign and magnitude of the parameter estimates are similar at the individual level and the aggregate (county) level; both showing pro-cyclical mortality.
Keywords: E3; I1; I12; 330; aggregation; income; death; recession; health; unemployment